Proceso de atención de enfermería en lactante con gastroenteritis aguda. - Mancilla Bernabe, Leonela Nicole (2022)
Acute gastroenteritis is a self-limited process that consists of reduced consistency and increased frequency of bowel movements, which can be accompanied by fever, vomiting, and abdominal pain. Its etiology is mainly of viral origin, with rotavirus as the main agent that produces diarrhea worldwide, caused by bacteria and parasites. The risk factors that favor severity and susceptibility are: Overcrowding, malnutrition and poor socioeconomic conditions. Infants and children under 5 years of age are more prone to dehydration. In the diagnosis of an infant and/or child with acute diarrhea, a global assessment and a detailed history are necessary in order to differentiate enteric infection from other causes that cause diarrhea and vomiting. Initial treatment of gastroenteritis in children under 5 years of age is rehydration. Next, the clinical case of an infant who is admitted to the Sacred Heart of Jesus Hospital with a diagnosis of acute Gastroenteritis will be analyzed, in order to provide the appropriate interventions to be followed as nurses with the intention of obtaining his speedy recovery and avoiding future complications in its development.